Low-cost virtual instrumentation applied to geotechnical testing - Contreras-Ferreyra, Dante Uriel; Martínez-Rojas, Alondra; Pastor-Gómez, Nelio; Chávez-Negrete, Carlos (European Public & Social Innovation Review, 2025)
Introduction: In many of the current geotechnical tests, there is a need to improve data acquisition protocols, in addition to optimizing test procedures. The present work proposes the evaluation of 3 convetional sensors in geotechnical tests. Methodology: The devices used were an S3C DC-DC linear variable differential transformer, the HC-SR04 ultrasonic distance sensor, and the SKU:SEN0193 capacitive soil moisture sensor. The general methodology consisted of the development of the communication protocol, interface, and display of readings for each device. Subsequently, the calibration and precision level of each sensor was obtained. Results: The precision and reliability of the sensors were expressed according to the linear fit, obtaining R2 correlation values ​​for all equipment. Discussion: The implemented systems allowed the detection of significant changes or trends in the behavior of the materials, obtaining satisfactory performances in most of the sensors, except for the moisture sensor SKU:SEN0193, which registered low precision. Conclusions: The use of sensors offers an alternative to improve some of the typical geotechnical tests. However, it is important to mention that a particular calibration must be carried out for each sensor to be used.